Implementation and application of solar energy in Nigeria - Dibia, B.I. (2019)
Nigeria is an exporting country and the electricity sector depends on gas, diesel and hydropower sources. Currently, the hydropower has replaced gas as the main source of energy due to climate change. Presently, the fossil fuels are expensive and limited due to scarce generation. This resulted into a power supply shortage that created a huge gap between the energy supply and demand. However, a new alternative energy source is required to complement the existing shortfall in supply of electricity in the country. Solar energy is a potential resource with huge availability for small and large-scale off-grid and grid-connected systems to be utilized in Nigeria. However, the high cost of Photovoltaic (PV) systems is one of the major problems identified and the current energy uses have limitations due to climate change. It affects conventional energy, hydropower and biomass which result to deforestation, desertification and water shortage/drought. This study focusing on economic, policy and technical perspectives investigated the possibility of using solar PV system to address challenges of electricity shortage and the affordability in order to meet electricity consumption with over 180 million populations and reduce the tendency of depending on diesel-fuel generators in the future in Nigeria. However, this study involved use of questionnaire method for data collection to understand the population perception about solar energy use with PV systems. The off-grid case studies were selected to determine the electricity generation, consumption and the payback period with mono and polycrystalline silicon PV types for the electricity generation. The RET Screen simulation software was adopted to analyse the amount of electricity output generated and the amount of emission reductions due to PV efficiency and accuracy. The innovative financing (PAYG) model was used to assess energy budget to ascertain energy consumption per user against blind decision due to cost based on the financial resource availability. The simulation results reveal more of electricity generation with the installed PV system at angle 150 degree. The monthly bills due to increased energy supply from the installed off-grid PV systems reduced from the utility grid electricity. The payback time for installed PV systems based on financial viability analysis shows reasonable, affordable, profitable and rewarding. In addition, the electricity cost from installed PV system generation and presently without subsidy is lower than the grid electricity based on cost of outages. Finally, the results based on proposed grid-connected PV power system, putting economic factor into consideration can be more feasible.